A review of recent research on the use of cellulosic fibres, their fibre fabric reinforced cementitious, geo-polymer and polymer composites in civil engineering. (1st May 2016) - Yan, Libo; Kasal, Bohumil; Huang, Liang
Abstract: Environmentally-friendly monofilament cellulosic fibres have been widely used as alternatives for conventional steel reinforcement within concrete. Recently, the use of cellulosic fibre fabrics and their fabric reinforced polymer composites as reinforcement materials within and/or outside of construction materials (e.g. concrete) has gained popularity due to their inexpensive cost and favourable specific mechanical properties compared with synthetic fibre fabrics (e.g. E-glass). This review presents a summary of recent development on cellulosic fibre Fabric Reinforced Cementitious (FRC) and Fabric Reinforced Geopolymer (FRG) composites, as well as their cellulosic Fabric Reinforced Polymer (FRP) composites as reinforcements of concrete, masonry and timber structures for civil engineering applications. This review covers: (1) properties (i.e. chemical composition, microstructure, mechanical properties and cost) of monofilament cellulosic fibres and their comparison with synthetic fibres, the relationship between fibre chemical composition and fibre mechanical properties, parameters affect fibre properties; (2) properties (e.g. fabrication of monofilament fibres to fabrics and structures) of cellulosic fibre fabrics, properties of polymer matrices, and properties (i.e. flexural, tensile, impact, insulation and fire properties) of cellulosic fabric FRP composites; and (3) properties (compressive, flexural and tensile and impact properties) of cellulosic FRC and FRG composites, and the properties of cellulosic FRP composites reinforced concrete, masonry and timber structures. In addition, the degradation mechanisms of cellulosic FRC and FRP are discussed. Furthermore, the durability of FRC, FRG and FRP composites are reviewed and the methods to improve the durability of FRC, FRG and FRP composites from the aspects of fibre modification and matrix modification are reviewed and summarized.